2017
DOI: 10.1007/s12283-017-0228-z
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of ball degradation events in professional tennis

Abstract: Tennis balls are acknowledged to degrade with use and are replaced at regular intervals during professional matches to maintain consistency and uniformity in performance, such that the game is not adversely affected. Balls are subject to the international tennis federation's (ITF) ball approval process, which includes a degradation test to ensure a minimum standard of performance. The aim of this investigation was to establish if the ITF degradation test can assess ball longevity and rate of degradation and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 11 publications
(20 reference statements)
2
9
0
Order By: Relevance
“…This tallies closely with other research, Lane et al found 318 racket impacts, on average, every 9 games [7], Figure 2 shows the distribution within the dataset. The aerodynamic performance of new and used balls was explored by examining first servesa relatively constrained delivery compared to open play.…”
Section: Methodssupporting
confidence: 89%
See 1 more Smart Citation
“…This tallies closely with other research, Lane et al found 318 racket impacts, on average, every 9 games [7], Figure 2 shows the distribution within the dataset. The aerodynamic performance of new and used balls was explored by examining first servesa relatively constrained delivery compared to open play.…”
Section: Methodssupporting
confidence: 89%
“…Whiteside et al [6] examined metrics that distinguish between lower and higher ranked players in the Australian Open. Lane et al [7] looked for differences in ball performance during ball degradation. Wei et al used sophisticated modelling and statistical techniques to try to predict shot outcomes [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The 90 • and 30.5 m·s −1 impact condition was selected to include impacts at 90 • whereby the surface of the ball was tracked throughout impact as opposed to partially tracked. The impact condition representing the mean surface impact angle and ball speed found during professional play [1] was included to provide a benchmark against a more typical impact scenario. To determine the maximum absolute strain for each element of the surface, the major and minor strains of the element were compared to determine the greatest absolute strain value.…”
Section: Resultsmentioning
confidence: 99%
“…Four impact angles and five ball speeds were selected (Table 3), predominantly based on the findings of [1,2], to best replicate the impact conditions experienced during professional play. A maximum of five impacts per ball ensured minimal degradation in ball performance and, predominantly, ensured optimal pattern quality for the GOM software to process, as this could be inhibited by marks and smudges to the stochastic pattern.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation